2020
DOI: 10.1002/ehf2.12917
|View full text |Cite
|
Sign up to set email alerts
|

Early rehabilitation after stroke: relationship between the heart rate variability and functional outcome

Abstract: Aims Impaired autonomic nervous system regulation is frequently observed in patients with stroke. The aim of this prospective study was to evaluate the impact of cardiac autonomic tone on functional outcome after the early post-stroke rehabilitation. Methods and results One hundred and three consecutive patients (67 ± 11 years, body mass index (BMI) 27.1 ± 5.4 kg/m 2 , 64% men) with ischaemic (84% of patients) and haemorrhagic stroke were studied. Depressed heart rate variability (HRV), as a surrogate marker o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…The role of the insular cortex in the regulation of cardiovascular function has been previously reported, showing that right hemisphere insular cortex stroke leads to an increase in sympathetic activity [ 61 , 62 ]. Another study, investigating the impact of cardiac autonomic tone on the clinical outcome in subacute stroke, showed an association between the depressed heart rate variability and impaired functional outcome after post stroke neurological rehabilitation [ 63 ]. Thus, central autonomic dysfunction may contribute to the development of cardiovascular complications in patients with acute stroke leading to an adverse clinical outcome.…”
Section: Cardio–cerebral Interactions After Acute Strokementioning
confidence: 99%
“…The role of the insular cortex in the regulation of cardiovascular function has been previously reported, showing that right hemisphere insular cortex stroke leads to an increase in sympathetic activity [ 61 , 62 ]. Another study, investigating the impact of cardiac autonomic tone on the clinical outcome in subacute stroke, showed an association between the depressed heart rate variability and impaired functional outcome after post stroke neurological rehabilitation [ 63 ]. Thus, central autonomic dysfunction may contribute to the development of cardiovascular complications in patients with acute stroke leading to an adverse clinical outcome.…”
Section: Cardio–cerebral Interactions After Acute Strokementioning
confidence: 99%
“…Scherbakov et al [16] evaluated activities of daily living using Barthel Index score in subacute stroke patients. Their results showed that patients with an increased Barthel Index score (+32%) presented higher time-domain values compared with patients with a lower increase in Barthel Index score (+8%) [16]. At baseline, our patients exhibited a high mean Barthel Index score (95.1 ± 8), and in this context, they could not have increased their Barthel Index score by more than 5%; the small increase could have been insufficient to modify HRV parameters.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the study by Arad et al [15] show that the higher the functional independence measure score, the higher the HRV values in stroke patients. In addition, Scherbakov et al [16] found that the evolution of motor and functional outcomes in poststroke patients (<6 months) could change, depending on the HRV values, that is improvements in Barthel Index, Modified Rankin Scale and Rivermead Motor Assessment scores are greater for stroke patients with a higher HRV than for stroke patients with a lower HRV.…”
Section: Introductionmentioning
confidence: 99%
“…Stroke may be followed by central autonomic dysfunction, [1,2] with an early occurrence of from 21.8% to 79%, [3][4][5] including cardiovascular, endocrine, inflammatory immune, digestive, urinary and other systems. [6,7] The clinical signs include brainheart syndrome, stress hyperglycemia, shoulder-hand syndrome and sweating problem, and severe instances may lead to sudden cardiac death.…”
Section: Introductionmentioning
confidence: 99%